A Randomized-Controlled Trial of EMDR Flash Technique on Traumatic Symptoms, Depression, Anxiety, Stress, and Life of Quality With Individuals Who Have Experienced a Traffic Accident - Yaşar, Alişan Burak; Konuk, Emre; Kavakçı, Önder; Uygun, Ersin; Gündoğmuş, İbrahim and Taygar, Afra Selma and Uludağ, Esra (Frontiers in Psychology, 2022)
The Flash Technique of Eye Movement Desensitization and Reprocessing (EMDR) is recognized to be used efficiently and securely to reduce the effects of unpleasant emotions linked with traumatic memories. Using a randomized controlled trial methodology, this study attempts to establish the efficacy of the EMDR Flash Technique. This study's sample includes of volunteers who were involved in traffic accidents and were given the randomized EMDR Flash Technique and Improving Mental Health Training for Primary Care Residents (mhGAP) Stress management module. The participants were given a sociodemographic data form, the Depression-Anxiety-Stress 21 scale (DASS-21), the Impact of Event Scale-Revised (IES-R), and the WHOQOL Quality of Life scale. Participants were evaluated with measurements before, after and one-month the application. The mean age of the participants was 36.20 (11.41) years and 82.1% (n=32) were female. The DASS-21 Anxiety (η²=0.085), IES-R Intrusion (η²=0.101), Avoidance (η²=0.124), Total (η²=0.147), and WHOQOL-BREF Psychological (η²=0.106) score improvements of the EMDR Flash Technique group were shown to be statistically significant when compared to the mhGAP group. However, no statistically significant difference in the DASS-21 Depression, Stress, Impact of Event Scale-Revised Hyperarousal WHOQOL-BREF General Health, Physical, Social Relationships, and Environment component scores was reported between the two groups. The present study's findings clearly demonstrate that the EMDR Flash technique, when applied to persons involved in traffic accidents, is successful in improving anxiety, intrusion, avoidance, total traumatic stress, and mental quality of life symptoms for at least one month. We believe that these findings will improve the reliability and applicability of the EMDR Flash Technique, which was tested for the first time in a clinical randomized controlled trial (RCT).